ANALISIS KINERJA PENGOLAHAN AIR LIMBAH PAVILYUN KARTIKA RSPAD GATOT SOEBROTO JAKARTA - Sumiyati, Sri; Imaniar, Imaniar (Universitas Diponegoro, 2007)
Hospitals produce solid waste and also wastewater, hazardous and non-hazardous. Pavilyun Kartika as a part of RSPAD Gatot Soebroto, produces wastewater that has characteristic like a domestic wastewater. The hazardous waste that produced by Pavilyun Kartika were managed by RSPAD Gatot Soebroto. In Pavilyun Kartika, wastewater with flows 52 m3/days comes from bathrooms for patients, laundry, public bathrooms, and also kitchen. Wastewater of Pavilyun Kartika contains high BOD, COD, and also Ammoniac, though still in save numbers, because still under the standard regulation for wastewater in Jakarta. Wastewater treatment plant in Pavilyun Kartika use extended aeration method, as part of biological treatment. The principal of the treatment are aeration, sedimentation, and chlorination.